ANALISIS LAPORAN KEUANGAN DENGAN MELIHAT RASIO LIKUIDITAS PADA PT. BANK DANAMON INDONESIA TBK TAHUN 2011-2015 - Elvera . (JURNAL KOMPETITIF, 2017)
The purpose of this study is to analyze the financial statements by measuring the level of liquidity at PT. Bank Danamon Indonesia Tbk by proxy to the value of Loan to Deposit Ratio (LDR). Liquidity is a matter to be considered by every Bank, especially PT. Bank Danamon Indonesia Tbk. Liquid company means the company can guarantee its debts with its current assets. The research method used is Quantitative Analysis (nonstatistik) and this type of research is descriptive. The results showed that the level of liquidity of PT. Bank Danamon Indonesia Tbk. During the period 2011-2015 tend to decline, especially in the last three years. So it can be concluded that the liquidity ratio fluctuates. Based on the results of research suggested to the management of PT. Bank Danamon Indonesia, Tbk. May increase future liquidity.Keywords: Financial Statement, Liquidity, Loan to Deposit Ratio (LDR)